One pot microwave synthesis of highly stable AuPd@Pd supported core–shell nanoparticles. (25th May 2018) - Howe, Alexander G. R.; Miedziak, Peter J.; Morgan, David J.; He, Qian; Strasser, Peter; Edwards, Jennifer K.
Abstract : A series of 1 wt% supported Au, Pd and AuPd nanoalloy catalysts were prepared via microwave assisted reduction of PdCl2 and HAuCl4 in a facile, one pot process. Abstract : A series of 1 wt% supported Au, Pd and AuPd nanoalloy catalysts were prepared via microwave assisted reduction of PdCl2 and HAuCl4 in a facile, one pot process. The resulting materials showed excellent activity for the direct synthesis of hydrogen peroxide from hydrogen and oxygen, with a synergistic effect observed on the addition of Au into a Pd catalyst. Detailed electron microscopy showed that the bimetallic particles exhibited a core–shell morphology, with an Au core surrounded by an Au–Pd shell, with a size between 10–20 nm. The presence of Au in the shell was confirmed by EDX studies, with corroborating data from XPS measurements showing a significant contribution of both Au and Pd in the spectra, with the Au signal increasing as the total Au content of the catalyst increased. No PdO was observed, suggesting a complete reduction of the metal chloride nanoparticles. Unlike similar catalysts prepared by sol-immobilisation methodology, the core–shell structures showed excellent stability during the hydrogen peroxide synthesis reaction, and no catalyst deactivation was observed over 4 reuse cycles. This is the first time the preparation of stable core–shell particles have been reported using microwave assisted reduction. The observation that these particles are core–shell, without the need of a complicated synthesis or high thermal treatment and form in just 15 minutes presents an exciting opportunity for this experimental technique.